SKRINING AKTIVITAS ANTIMIKROBA EKSTRAK HERBA BELIMBING TANAH (OXALIS CORNICULATA L.) SECARA KLT-BIOAUTOGRAFI DAN DIFUSI AGAR - Herwin, Herwin; Nuryanti, Siska (Fakultas Farmasi UMI, 2012)
The screening studies have been carried out antimicrobial activity of herb Belimbing Tanah (Oxalis corniculata L.) extracts from Mamuju West Sulawesi that purpose to got data about activity of Belimbing Tanah (Oxalis corniculata L.) extract based on antimicrobial screening of some microbes in the Bioautography-TLC test and agar diffusion.The result screening of antimicrobial activity by Bioautography-TLC,showed that dietil eter extract of belimbing tanah (Oxalis corniculata L.) give antimicrobial activity to bacteri Staphylococcus aureus, Streptococcus mutans, Staphylococcus epidermidis, Salmonella thypi, Escherichia coli, Vibrio sp, and fungus Candida albicans with a profile chromatogram using the eluent n-hexane: ethyl acetate Rf value of 0.45 obtained. And the screening of antimicrobial activity of the juice belimbing tanah (Oxalis corniculata L.) at a concentration of 25%, 50% and 75% in the diffusion in order to obtain an average diameter of zone of resistance to the bacteria Staphylococcus aureus = 14:00 mm, Streptococcus mutans = 15.00 mm, Salmonella thypi = 24.66 mm, Escherichia coli = 19.99 mm, Vibrio sp = 17.77 mm, and fungus Candida albicans = 15.00 mm. Keyword : Oxalis corniculata L., Screening of antimicrobial, Mamuju